Analysis of Economic Vulnerability and Resilience of Communities Affected by Floods in Central Tapanuli, North Sumatra, and Aceh - Bambang Sugiharto; H. Harkim; Maya Andriani; Syah Paradiba S. Sirait; Rejekia Vaizal Simanungkalit (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines the economic vulnerability and resilience of flood-affected communities in Central Tapanuli, North Sumatra, and Aceh through a qualitative literature review based on published articles, reports, and relevant policy documents. The study analyzes key dimensions of vulnerability, including poverty, livelihood dependence, limited financial access, housing conditions, disaster exposure, and adaptive capacity. The findings show that economic vulnerability is strongly influenced by dependence on climate-sensitive livelihoods, weak household assets, and limited access to savings, credit, insurance, and formal recovery assistance. Although affected communities demonstrate adaptive responses such as temporary relocation, livelihood diversification, housing modification, social capital utilization, and informal cooperation networks, overall community resilience remains relatively weak, particularly in social and institutional dimensions. The study highlights that flood management policies should move beyond short-term emergency relief toward integrated strategies that strengthen local economic capacity, adaptive social protection, community-based early warning systems, and sustainable livelihood diversification. These findings contribute to disaster risk reduction studies by emphasizing the need for inclusive, locally grounded, and multidimensional policy responses to reduce flood-related economic vulnerability.